DATA ACQUISITION SYSTEM THROUGH THE INTERNET NETWORK CASE STUDY ROOM TEMPERATURE MEASUREMENT WITH SENSOR DS1621 - Indrianto Indrianto (JAKSTIK Journal, 2005)
Sensor in industrial and other much needed because with the sensor adannya industrial areascan be easily able to control equipment remotely. The sensor can be used if there is a series ofADC and DAC, and required a calibration for the sensor can measure an exact quantity. Byusing DS1621 sensors then it is not necessary because the DS1621 is a sensor that 'smart'(Intelegent sensor). DS1621 does not require the microcontroller and does not requirecalibration.Temperature Measuring Equipment Design Room With DS1621 Sensor Networks ThroughInternet-Based Personal is a tool for censorship that uses DS1621 temperature. Data sent bythe temperature sensor can be taken via the Internet network so that this equipment can beaccessed from anywhere as long as it is connected to the internet. This circuit has atemperature of 125 C-20 .......+ Software used to display the results of temperaturemeasurement is HTML. Use the Windows 2000 server as a server on this design is veryhelpful. Since making almost all computer activity becomes easier, faster and fully integratewith the Internet because there are DNS (Domain Name System) and IIS (InternetInformation Service).